Evaluation of the effects of phototherapy on cochlear function in newborns - Polat, Cahit; Aydin, Mustafa; Sakallioglu, Oner; Akyigit, Abdulvahap; Unsal, Selim; Soylu, Erkan; Keles, Erol (Elsevier Ireland Ltd, 2014)
Objective: This study aimed to evaluate any potential effects of phototherapy on cochlear function in newborns using transient evoked otoacoustic emissions (TEOAEs). Methods and materials: Fifty-seven newborns, undergoing phototherapy for hyperbilirubinemia without any other risk factors, and a control group of 53 healthy newborns, were administered the TEOAE test prior to and following phototherapy. In the newborns undergoing phototherapy, otoacoustic emission (OAE) measurements obtained at baseline and following phototherapy were compared. Moreover, pre-phototherapy OAE measurements obtained in the newborns undergoing phototherapy were compared with the OAE measurements of the control group. Results: In newborns undergoing phototherapy, there was no significant difference between pre- and post-phototherapy TEOAE amplitudes, nor in the reproducibility ratios. Similarly, no difference was found in the pre-treatment measurements of amplitude and reproducibility ratios between phototherapy-receiving newborns and controls (p > 0.05). Conclusion: The normal TEOAE results observed in the newborns undergoing phototherapy suggest that phototherapy does not exert negative effects on the cochlea. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Phototherapy; Hyperbilirubinemia; Hearing; Cochlea; Otoacoustic emissions; Newborn